2001
DOI: 10.1007/s002100000369
|View full text |Cite
|
Sign up to set email alerts
|

The cloned human 5-HT 7 receptor splice variants: a comparative characterization of their pharmacology, function and distribution

Abstract: Serotonin (5-hydroxytryptamine, 5-HT) receptor pre-mRNA is alternatively spliced in human tissue to produce three splice variants, h5-HT7(a), h5-HT7(b) and h5-HT7(d), which differ only in their carboxyl terminal tails. Using membranes from transiently and stably transfected HEK293 cells expressing the three recombinant h5-HT7 splice variants we compared their pharmacological profiles and ability to activate adenylyl cyclase. Using PCR on cDNA derived from various human tissues, the 5-HT7(a) and 5-HT7(b) splice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
156
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(161 citation statements)
references
References 33 publications
4
156
0
1
Order By: Relevance
“…Plasmids-The pcDNA3.1(Ϫ) vectors encoding the human 5-HT 4(b) and 5-HT 7(a) receptors were described previously (39,40). The pcDNA3.1 vector encoding the dominant negative Rap1, RapN17, was provided by Dr. Philip J. S. Stork (Oregon).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids-The pcDNA3.1(Ϫ) vectors encoding the human 5-HT 4(b) and 5-HT 7(a) receptors were described previously (39,40). The pcDNA3.1 vector encoding the dominant negative Rap1, RapN17, was provided by Dr. Philip J. S. Stork (Oregon).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, there is a need to determine whether 5-HT 4 and 5-HT 7 receptors can activate ERK, as well as the mechanism for such activation. We have previously characterized activation of adenylyl cyclase by different splice variants of the human G s -coupled 5-HT 4 (39) and 5-HT 7 (40) receptors. We now demonstrate that both the human G s -coupled serotonin receptors 5-HT 4(b) and 5-HT 7(a) , when transiently expressed in HEK293 and COS-7 cells, activate ERK1/2 through a mechanism dependent on Ras and independent of Rap1.…”
mentioning
confidence: 99%
“…In addition to its effect on 5-HT 2 receptors, Ritanserin is also a 5-HT 7 antagonist. However, the affinity for 5-HT 2 receptors is much higher than for 5-HT 7 receptors (Hoyer et al, 1993;Krobert et al, 2001). Any possible effect on 5-HT 7 receptors (i.e., increase in generation of TH-ir cells) may therefore be counteracted by the effect on 5-HT 2 receptors (i.e., decrease in generation of TH-ir cells).…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] Immunohistochemistry studies have pinpointed co-expression of A, B, C, D, and E subunits in enterocytes and also the nerves of the myenteric plexus 24,27 indicating that heteromeric 5-HT 3 receptors are likely to form in the human colon. Although 5-HT 4 and 5-HT 7 receptor splice variants have been identified in separate studies in the small intestine and colon, 22,[28][29][30] no study has looked at their tissue distribution along the colon. However, one earlier study showed that the 5-HT 3 receptor subunit transcript distribution differed in the sigmoid colon 22 providing evidence that specific subunits may be potential targets.…”
Section: Introductionmentioning
confidence: 99%